Discriminatory behavior towards Women in Educational Sphere: A Case Study of Kashi Noble Academy, Siddartha Nagar, Rupandehi - Kain, Tika Raj; Dhakal, Naba Raj (NUTA Journal, 2023)
The paper aims to assess gender discrimination in private educational institution in Nepal. This study argues that female teachers are discriminated in institutional structure in multiple ways. It applies descriptive and exploratory research design. Both primary and secondary data have been collected and qualitative and quantitative nature of data are employed. Interview schedule has been selected to collect the data from the field. Women are discriminated in the process of recruitment, training and development, and remuneration. The paper contributes to the study of gender discrimination from sociological vantage point because this emphasizes that gender is socially and historically constructed and the social structure and institutions are responsible to exercise gender discrimination. It, however, does not incorporate the broad spectrum in regards with theory and methods.